Simpson–Golabi–Behmel syndrome in a 39‐year‐old male patient with suspected acromegaly—A case study. Issue 2 (28th December 2018) - Andrysiak‐Mamos, Elżbieta; Sagan, Karol Piotr; Lietz‐Kijak, Danuta; Kijak, Edward; Kaźmierczak, Beata; Pietrzyk, Aleksandra; Sowinska‐Przepiera, Elżbieta; Sagan, Leszek; Syrenicz, Anhelli
Abstract: Simpson–Golabi–Behmel syndrome (SGBS) is a rare genetic condition and is inherited in an X‐linked recessive manner. The disease is caused by a change in the nucleotide sequence of an X‐linked gene encoding glypican 3, a protein belonging to the heparan‐sulfate membrane proteoglycan family. SGBS case studies are almost entirely restricted to the pediatric population. Scarce literature describing SGBS course in adults may be due to both the high mortality of SGBS patients in childhood and low rate of SGBS diagnosis in adults. We present a case of a 39‐year‐old man with an initial diagnosis of acromegaly. Genetic tests revealed a hitherto unreported deletion in the GPC3 gene. SGBS manifestations in our patient included tall stature, dysmorphic features, and central nervous system (CNS) anatomical pathology. MRI of the head visualized abnormalities of median line structures, a feature consistent with SGBS: an unclosed craniopharyngeal canal, a sellar‐suprasellar cyst, dysmorphic pituitary gland, and a cyst of the septum pellucidum. Moreover, cardiomyopathy complicated by life‐threatening paroxysmal ventricular tachycardia was diagnosed. Although various cardiac anomalies are often found in SGBS, their pathogenesis is unclear and may be multifactorial. We believe that the presented case contributes to a better understanding of SGBS and may help clinicians in introducing prophylaxis and treatment for its comorbidities.